Upaya Hukum Korban Kegiatan Outing Class Yang Mengakibatkan Korban Jiwa Dikategorikan Sebagai Perbuatan Melawan Hukum - Sakti, Dimas Bayu; Wahjoeono, Dipo (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to examine whether casualties arising from outing class activities both fatalities and victims experiencing physical or psychological trauma can be categorized as unlawful acts. It also seeks to identify the legal remedies available to victims and their families as the disadvantaged parties in holding the responsible institution accountable for material and immaterial losses. Although outing class activities are intended to enhance students’ creativity, skills, and learning experiences through outdoor learning, they have increasingly received negative public stigma when such activities result in tragedies causing loss of life. These incidents raise parental concerns regarding student safety, prompting victims and their families to pursue legal measures as a form of protection and to ensure equal treatment before the law. This research employs a normative juridical approach, examining legal provisions, norms, and doctrines relevant to the issues addressed. The study concludes that the actions of the school can be classified as unlawful acts when assessed against the established legal elements and the facts of the incident. Consequently, the school bears legal responsibility for the harm caused by the negligence of its employees, particularly teachers, in organizing outing class activities. Accountability includes providing compensation for both material and immaterial damages suffered by the victims.